Amplified singlet oxygen generation in metallated-porphyrin doped conjugated polymer nanoparticles - Spada, Ramiro Martín (2018)
We report on the mechanism and efficiencies of singlet oxygen O2(1Δg) generation of nanoparticles (NP) of the conjugated polymer (CP) poly(9,9-dioctylfluorene-alt-benzothiadiazole) (F8BT) doped with platinum octaethylporphyrin (PtOEP) suspended in water. A detailed study of the photophysics of these NP, using stationary and time-resolved absorption and emission techniques, indicates that O2(1Δg) is generated by the triplet excited state of F8BT and not by that of PtOEP, as previously observed for other porphyrin doped CP NP. O2(1Δg) quantum yields (ΦΔ) were measured by quantifying the characteristic phosphorescence of O2(1Δg) in the NIR region (∼1268 nm). It was found that incorporation of relatively small amounts of PtOEP to F8BT NP results in a significant increase of ΦΔ. NP containing 10% PtOEP (w/w) show a ΦΔ ∼ 0.24, which is 3 times larger than that observed for undoped F8BT NP, and larger than the reported for most water-soluble porphyrins. ΦΔ were also calculated from the oxidation rates (v0) of 3-[10-(2-carboxyethyl)anthracen-9-yl]propanoic acid (ADPA), a well-known chemical O2(1Δg) trap. Unexpectedly, this method was found to significantly overestimate the ΦΔ values due to the adsorption of ADPA on the surface of NP. The ADPA/NP adsorption process was characterized using a simple adsorption model yielding an (average) equilibrium constant of ∼8 × 103 M−1 and an (average) number of NP-binding sites of ∼14000. These results necessarily caution about the use of ADPA as a probe to evaluate ΦΔ in these NP systems. In addition, the interaction of F8BT NP with other anionic, cationic and zwitterionic dyes (dissolved in water) was studied. It was found that even at nano-molar concentrations all the dyes efficiently adsorb on the NP surface. This general and simple self-assembly strategy can be used to prepare superficially-dye-doped CP NP with potentially interesting technological applications.